2006
DOI: 10.1063/1.2198103
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium scandate thin films as an alternative gate dielectric prepared by electron beam evaporation

Abstract: Gadolinium scandate thin films deposited on silicon substrates using electron beam evaporation were investigated. Measurements with Rutherford backscattering spectrometry, high temperature x-ray diffraction, x-ray reflectometry, transmission electron microscopy, and atomic force microscopy were performed. A stoichiometric transfer of material from the source to the substrate in high vacuum could be demonstrated. Homogeneous, amorphous, and smooth films ͑root mean square surface roughness Ͻ1 Å͒ stable up to 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
54
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 6 publications
5
54
1
Order By: Relevance
“…From the slope of the linear fit, it is possible to calculate the dielectric constant ͑ ͒ of the films excluding the contribution of a lower-interfacial layer. The value obtained for the LaLuO 3 films is Ϸ32, which is higher than those obtained for other amorphous rare earth oxide films 4,5 and amorphous HfO 2 films 13 exhibiting = 22-23. The intersection between the CET axis and the linear fit at 2.6 nm indicates the existence of a lower-interfacial layer between the LaLuO 3 film and the Si substrate.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…From the slope of the linear fit, it is possible to calculate the dielectric constant ͑ ͒ of the films excluding the contribution of a lower-interfacial layer. The value obtained for the LaLuO 3 films is Ϸ32, which is higher than those obtained for other amorphous rare earth oxide films 4,5 and amorphous HfO 2 films 13 exhibiting = 22-23. The intersection between the CET axis and the linear fit at 2.6 nm indicates the existence of a lower-interfacial layer between the LaLuO 3 film and the Si substrate.…”
mentioning
confidence: 64%
“…The electrical characterization reveals good C-V behavior, a low leakage current density, and a value of about 32, which is larger than those previously determined for other alternative high-amorphous oxides ͑ =22-23͒. 4,5,13,14 One of the authors ͑J.M.J.L.͒ gratefully acknowledges the Alexander von Humboldt Foundation for a research fellowship. The authors thank P. Meuffels for postannealing the target material.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…7,8 In contrast, rare earth ͑RE͒ scandates ͑REScO 3 , RE=Gd, Dy, La͒ show higher and, therefore, have attracted significant attention for high-applications. [9][10][11][12][13] The amorphous RE scandates have between 20 and 30 and the crystalline phases have over 30. 12 Christen et al observed band gaps higher than 5.5 eV for these REScO 3 oxides and varying crystallization temperatures depending on the RE atomic number and the Goldschmidt tolerance factor.…”
mentioning
confidence: 99%